Are females in classical hematology getting a fair share? Uncovering gender disparities in NIH R01 grants - Khan, Sara; Eshaghi, Faraz; Rehman, Mohammed Z.; Kotwal, Serena; Syed, Mariya; Khan, Kainat; Kumar, Kapisthalam S. (Frontiers in Sociology, 2024)
Gender Disparity remains a pressing issue in academic medicine, notably in classical hematology where females continue to be underrepresented by the National Institutes of Health (NIH) for funded R01 grants. In this research, we analyzed ten years of NIH R01 grants funded in classical hematology, covering the period from 2012 to 2022. Of the 250,031 R01 grants funded during this period, females received only 32.9%. Further breakdown of the data by different NIH institutes highlights varying degrees of gender gaps, with specific institutes showing pronounced disparities. While some NIH Institutes have made progress in bridging the gap, others lag, indicating a need for a closer examination of institutional practices. We found that despite modest advancements, less than 50% of R01 grants were funded to females. These findings underscore persistent gender inequity and require concerted efforts to create a more inclusive atmosphere supportive of women’s progress in academic medicine.